Predictors of the Failure of Noninvasive Ventilation in Patients With Acute Respiratory Failure Caused by Severe Acute Pancreatitis: A Prospective Observational Study. Issue 8 (September 2021) - Shu, Weiwei; Huang, Tao; Jiang, Ting; Bai, Linfu; Han, Xiaoli; Huang, Shicong; Duan, Jun
Abstract : Objective: The aim of the study was to identify risk factors associated with the failure of noninvasive ventilation (NIV) in patients with severe acute pancreatitis (SAP). Methods: Patients who received NIV as a first-line therapy because of acute respiratory failure caused by SAP were enrolled. Results: A total of 133 patients were enrolled. Of the patients, 32 (24%) experienced NIV failure. Male sex (odds ratio [OR], 4.25; 95% confidence interval [CI], 1.48–12.22), older age (OR, 1.04; 95% CI, 1.01–1.08), a higher Acute Physiology and Chronic Health Evaluation II score (OR, 1.18; 95% CI, 1.03–1.36), and a procalcitonin level greater than 3.8 ng/mL (OR, 6.28; 95% CI, 2.04–19.31) were independently associated with NIV failure. The receiver operating characteristic curves for predicting NIV failure were 0.67, 0.72, and 0.76 tested by age, procalcitonin, and Acute Physiology and Chronic Health Evaluation II score, respectively. From initiation to 24 hours, the patients in the NIV failure group had a higher proportion of Glasgow Coma Scale scores of 14 or less, a higher proportion of pH ≤7.35, and higher respiratory rates than ones in the successful NIV group. Conclusions: One of 4 SAP patients experience NIV failure. Age, sex, disease severity, level of inflammation, and vital signs can be used to predict NIV failure.